Spin trapping of nitric oxide by ferro-chelates: kinetic and in vivo pharmacokinetic studies - Pou, Sovitj; Tsai, Pei; Porasuphatana, Supatra; Halpern, Howard J.; Chandramouli, G.V.R.; Barth, Eugene D.; Rosen, Gerald M. (Biochimica et biophysica acta, 1999)
Biologically generated nitric oxide appears to play a pivotal role in the control of a diverse series of physiologic functions. Iron-chelates and low-frequency EPR spectroscopy have been used to verify in vivo production of nitric oxide. The interpretation of in vivo identification of nitric oxide localized at the site of evolution in real time is complicated by the varied kinetics of secretion. The quantitative efficiency of the spectroscopic measurement, so important in understanding the physiology of nitric oxide, remains elusive. The development of a more stable iron-chelate will help better define nitric oxide physiology. In this report, we present data comparing the commonly used ferro-di( N-methyl- d-glucamine-dithiocarbamate) (Fe 2+(MGD) 2) and the novel chelate ferro-di( N-(dithiocarboxy)sarcosine) (Fe 2+(DTCS) 2) quantifying the in vitro and in vivo stability of the corresponding spin trapped adducts, NO-Fe(MGD) 2 and NO-Fe(DTCS) 2. Finally, very low frequency EPR spectroscopy has been used to evaluate the pharmacokinetics of NO–Fe(MGD) 2 and NO–Fe(DTCS) 2 in mice in real time.